The impact of education and occupation on cognitive impairment: a cross-sectional study in China - Zhong, Tangsheng; Li, Shiyuan; Liu, Peiqi; Wang, Yonghong; Chen, Li (Frontiers in Aging Neuroscience, 2024)
Background and objectives Education, occupation, and cognitive activity are key indicators of cognitive reserve and are thought to influence cognitive impairment. However, the individual and combined impacts of these factors are not fully understood. This study aims to investigate the roles of education and occupation in cognitive impairment while controlling for brain reserve and cognitive activity. Methods This cross-sectional study involved 369 participants aged 50 years or older from urban outpatient clinics in Jilin Province, China. Cognitive impairment was assessed using neuropsychological scales and brain imaging. Cognitive activity was evaluated with the Cognitive Reserve Scale (CRS). Covariance analysis and logistic regression models were used to analyze the associations, adjusting for age, sex, education, and occupation. Results Higher education was significantly associated with a lower risk of cognitive impairment (p < 0.001), regardless of occupation. In contrast, occupational complexity and cognitive activity did not show a significant relationship with cognitive impairment (p > 0.05). Conclusion Education, rather than occupation or cognitive activities, is a significant predictor of cognitive impairment, highlighting the importance of educational attainment in cognitive health.